2008
DOI: 10.1007/s10350-007-9180-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function, Body Image, and Quality of Life after Laparoscopic and Open Ileal Pouch-Anal Anastomosis

Abstract: After ileal pouch-anal anastomosis, men and women reported excellent body image and high cosmetic and quality of life scores regardless of operative approach. Female sexual function was more adversely affected after ileal pouch-anal anastomosis than was male sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 30 publications
4
74
1
1
Order By: Relevance
“…Finally, as observed in open series, the use of laparoscopy in patients with or without previous colectomy did not modify either morbidity or functional results. Other expected benefits of laparoscopy, already demonstrated for colectomy but not assessed specifically in our study (i.e., cosmetic, body image [37], postoperative pain, early return to normal activity, etc. ), and the long-term benefit in IPAA patients (i.e., possible reduction of adherences and infertility) should be demonstrated in the future by larger studies.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, as observed in open series, the use of laparoscopy in patients with or without previous colectomy did not modify either morbidity or functional results. Other expected benefits of laparoscopy, already demonstrated for colectomy but not assessed specifically in our study (i.e., cosmetic, body image [37], postoperative pain, early return to normal activity, etc. ), and the long-term benefit in IPAA patients (i.e., possible reduction of adherences and infertility) should be demonstrated in the future by larger studies.…”
Section: Discussionmentioning
confidence: 92%
“…This small study showed no difference in functional outcome and qualityof-life scores between the two contrasting approaches to treatment. The Mayo group [20] examined a larger subset; 125 of 289 patients (43% responders) were questioned 1 year after operation to evaluate sexual function, body image, and quality of life. There were no significant differences in terms of demographics, complications, or long-term functional outcomes between responders and nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported our results in patients who have undergone both minimally invasive and open IPAA at our institution. 32 We found that overall QOL was excellent and equal between open and minimally invasive patients. Moreover, regardless of technique, patients had higher than normative values for the U.S. population.…”
Section: Sexual Function and Quality Of Life After Ipaamentioning
confidence: 95%